Kaizen costing in delphi technologies - Carvalho, Frederico Manuel da Cruz Ramalho Duarte de (2021)
Background: This study investigates how Kaizen Costing can aid in the cost savings process in material for Delphi Technologies, where a complete breakdown of the general process is given, as well as a real-life example. Methods: The paper consists of an interventionist research case study. Qualitative and quantitative data was gathered to outline the exact cost saving process. Results: The design change boosted company’s savings by $ 761,249 for a period of twelve months. Conclusion: Findings offer unique insights to the impact Kaizen Costing has on material cost savings, which augments its competitiveness in the fierce automotive industry.